016 Long-term disease stability in patients treated with cladribine tablets in CLARITY and CLARITY extension. Issue 6 (27th May 2022) - Giovannoni, Gavin; Comi, Giancarlo; Rammohan, Kottil; Rieckmann, Peter; Vermersch, Patrick; Dangond, Fer- nando; Keller, Birgit; Jack, Dominic
Abstract : Background: This post-hoc analysis evaluated long-term disease stability of relapsing-remitting multiple sclerosis (RRMS) patients, according to Expanded Disability Status Scale (EDSS), after treatment with clad- ribine tablets 10mg (cumulative dose 3.5mg/kg [CT3.5] over 2 years) in CLARITY and CLARITY Extension. Methods: Patients randomised to CT3.5 in CLARITY then placebo in CLARITY Extension, with ≥1 post- baseline EDSS measurement, were included (CP3.5, n=98). EDSS score over time (CLARITY randomisation to end of follow-up in CLARITY Extension, including the bridging interval between studies) was assessed at 6-month intervals, and separately at time to 3- and 6-month confirmed EDSS score progression from CLARITY baseline. Results: Five years after CLARITY baseline, median EDSS remained stable compared with baseline. Median EDSS score (95%CI) for CP3.5 was 2.5(2.0–3.5) vs 3.0(2.5–3.5) at baseline. In each 12-month period, EDSS score was stable in >50% of patients, 21–30% improved and 0–25% worsened. During Year 5, EDSS was stable in 53.9% of patients, 21.3% improved and 24.7% worsened; <30% of patients reached 3- or 6-month confirmed EDSS progression. Conclusions: EDSS score was stable up to 5 years post-CLARITY baseline for CP3.5 patients. Between 20–30% of patients demonstrated improvement in EDSS score vs baseline each year. CLARITY: NCT00213135 . CLARITY Extension: NCT00641537 g.giovannoni@qmul.ac.uk